2016
DOI: 10.18632/oncotarget.10508
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic ligands of death receptor 5 display a cell-selective agonistic effect at different oligomerization levels

Abstract: DR4 (Death Receptor 4) and DR5 (Death Receptor 5) are two potential targets for cancer therapy due to their ability to trigger apoptosis of cancer cells, but not normal ones, when activated by their cognate ligand TRAIL (TNF related apoptosis-inducing ligand). Therapies based on soluble recombinant TRAIL or agonist antibodies directed against one of the receptors are currently under clinical trials. However, TRAIL-R positive tumor cells are frequently resistant to TRAIL induced apoptosis. The precise mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In accordance with results from earlier studies (19), the assembly of two scTRAIL moieties into a hexavalent molecule considerably increased activation of caspases and subsequent cell death compared with trivalent scTRAIL. Of note, recent data highlighted the importance not only of increased valency, but also of an appropriate spatial organization to allow multivalent receptor binding (33). Our results demonstrate that employing a single-chain version of the natural homotrimeric TRAIL ligand in the context of immunoglobulin-derived dimerization modules enables potent death receptor activation.…”
Section: Discussionmentioning
confidence: 60%
“…In accordance with results from earlier studies (19), the assembly of two scTRAIL moieties into a hexavalent molecule considerably increased activation of caspases and subsequent cell death compared with trivalent scTRAIL. Of note, recent data highlighted the importance not only of increased valency, but also of an appropriate spatial organization to allow multivalent receptor binding (33). Our results demonstrate that employing a single-chain version of the natural homotrimeric TRAIL ligand in the context of immunoglobulin-derived dimerization modules enables potent death receptor activation.…”
Section: Discussionmentioning
confidence: 60%
“…We previously described two cyclic peptides, named 1m and 2m in their monovalent forms that only differ by the position of a lysine in their sequence (see Supplementary Materials ). Their divalent forms, known as 1d and 2d respectively, bound to TRAIL-R2 with high affinity as measured by SPR and induced apoptosis of various cell lines [ 27 , 28 ]. In the present study, we compared the pro-apoptotic activity of 1d and 2d on the human Burkitt lymphoma BJAB, T leukemia Jurkat and the colon carcinoma HCT116 cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…We previously described synthetic peptides (1 and 2) targeting the TRAIL-R2 receptor and that induce TRAIL-R2-dependent apoptosis of BJAB cells, in divalent and trivalent forms [ 27 ]. SPR experiments indicated that both 1d and 2d formed stable complexes with recombinant TRAIL-R2 covalently immobilized on a sensor surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical shift assignment has been used to perform binding studies with TRAILmim peptidomimetics that bind to DR5 (Pavet V et al, 2010;Pulka-Ziach K et al, 2015;Beyrath J et al, 2016) and the results will be reported in a future publication.…”
Section: Biological Contextmentioning
confidence: 99%